Rejecting Empathy for Animal Ethics - Kasperbauer, T. J. (Ethical theory and moral practice, 2015)
Ethicists have become increasingly skeptical about the importance of empathy in producing moral concern for others. One of the main claims made by empathy skeptics is a psychological thesis: empathy is not the primary psychological process responsible for producing moral concern. Some of the best evidence that could confirm or disconfirm this thesis comes from research on empathizing with animals. However, this evidence has not been discussed in any of the prominent critiques of empathy. In this paper, I investigate six different empirical claims commonly made about empathy toward animals. I find all six claims to be problematic, though some are more plausible than others, and argue that empathy is indeed not psychologically central to producing moral concern for animals. I also review evidence indicating that other moral emotions, particularly anger, are more strongly engaged with producing moral concern for animals, and are thus more capable of achieving various normative aims in animal ethics. The conclusion of my argument is that empathy should lose its currently privileged place.